Analisis Tantangan Bagi Kesehatan Gender Terhadap Hak Pada Manusia - Faturrohman Faturrohman; M. Abdur Rahman (Lembaga Pengembangan Kinerja Dosen, 2024)
Challenges to the rights possessed by humans can cover various complex and various kinds, such as social, political, and economic. There are challenges such as freedom of opinion and the existence of the press, where even though freedom of the press has been recognized, there is still pressure and intimidation against journalism. Cases such as arrests and violence against journalists who cover this sensitive issue often occur. There are land conflicts between indigenous communities and large companies (especially in the plantation and mining sectors), which can often result in forced evictions. These laws can often be used to further suppress freedom of religion and speech, and have led to many people being imprisoned on charges of blasphemy. Many workers in the informal and formal sectors experience poor working conditions, including low wages, long hours, and a lack of occupational health and safety protection.